Yamada-Watanabe theorem for stochastic evolution equations in infinite dimensions - M.Röckner; B.Schmuland; X.Zhang (Condensed Matter Physics, 2008)
The purpose of this note is to give a complete and detailed proof of the fundamental Yamada-Watanabe Theorem on infinite dimensional spaces, more precisely in the framework of the variational approach to stochastic partial differential equations.